2013
DOI: 10.1371/journal.pone.0070569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controlled-Release Fertiliser on Nitrogen Use Efficiency in Summer Maize

Abstract: Nitrogen (N) is a nutrient element necessary for plant growth and development. However, excessive inputs of N will lead to inefficient use and large N losses to the environment, which can adversely affect air and water quality, biodiversity and human health. To examine the effects of controlled-release fertilisers (CRF) on yield, we measured ammonia volatilisation, N use efficiency (NUE) and photosynthetic rate after anthesis in summer maize hybrid cultivar Zhengdan958. Maize was grown using common compound fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 28 publications
6
47
0
2
Order By: Relevance
“…For instance, researchers have already found that adopting drip irrigation, optimizing fertilizer application methods, and using controlled release fertilizer, etc. can reduce the carbon footprint effectively (Ellert and Janzen, 2008;Ye et al, 2013;Zhao et al, 2013a). Furthermore, direct emissions of nitrous oxide from the field accounted for 2.6e9.8% of total GHG emissions.…”
Section: Composition Of Ghg Emissionsmentioning
confidence: 99%
“…For instance, researchers have already found that adopting drip irrigation, optimizing fertilizer application methods, and using controlled release fertilizer, etc. can reduce the carbon footprint effectively (Ellert and Janzen, 2008;Ye et al, 2013;Zhao et al, 2013a). Furthermore, direct emissions of nitrous oxide from the field accounted for 2.6e9.8% of total GHG emissions.…”
Section: Composition Of Ghg Emissionsmentioning
confidence: 99%
“…Furthermore, increasing the frequency of top‐dressing applications is usually unacceptable due to practical and economic reasons. The application of controlled release fertilizer could release N gradually to coincide with the N demand of the crop (Grant et al., 2012; Ye et al., 2013) and has been proven to increase the grain yield and NUE of maize compared with conventional urea by several studies (Diez et al., 1994; Hu et al., 2013; Zhao, Dong, Zhang, & Liu, 2013; Zheng et al., 2017). Previous research on fertilization and planting densities focused on common fertilizer, however, there have been few attempts to evaluate the effects of slow‐released fertilizer on post‐silking N uptake and translocation, SLN, NUE, and grain yield in comparison with conventional fertilizer under different plant densities.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N), phosphorous (P), and potassium (K) are critical nutrient elements for crop plant growth and development, and applying fertilizers, especially N to crops, is a valuable agronomic practice (Zhao et al, 2013). However, excessive fertilization can result in nutrient inefficiencies and excessive losses of N and P in the field environment, and also impact soil, water and air quality, human health, and biodiversity (Goulding et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled-release fertilizer (CRF) is a good alternative to soluble fertilizer (SF) to increase FUE and minimize nutrient losses, especially N, in the field environment (Zhao et al, 2013). The coating material types of CRF play a key role in gradually releasing the nutrient (Li et al, 2012), and the most important parameters for controlling nutrient release include the thickness of the coating membrane, followed by temperature, granule radius, soil microbial activity, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation